EFFECT OF LUMOSITY TRAINING SCHEDULE ON RECALL OF NONSENSE SYLLABLES - KPOLOVIE, Peter James (Advances in Social Sciences Research Journal, 2018)
Randomized between subjects before-after experimental research design was adopted for incontestable establishment of cause-and-effect relationship between Lumosity training schedule and recall of nonsense syllables, if it exists. Learning is mainly a function of memory or recall. A random sample of 150 Tenth Grade students, each aged 15 years, was drawn for the investigation. They were randomized into five groups assigned different schedule of Lumosity Training as experimental conditions (daily 00, 06, 12, 18, and 24 minutes Lumosity training). The experimental treatment lasted for 60 days that was judged long enough for the training to cause some changes in the subjects, if at all Lumosity training could positively or negatively affect the subjects’ memory or recall ability. The 60 brands of Lumosity brain enhancement games used as treatment conditions fall under seven different skills categories (8 on Problem-solving skills, 9 on Flexibility skills, 9 on Speed skills, 11 on Attention skills, 13 on Memory skills, 5 on Math skills, and 5 on Language skills). Results of data analysed with Analysis of covariance (ANCOVA) showed statistically significant effect of Lumosity training schedule on recall of nonsense syllables when the effect of the nonsense syllables Pre-test has been held constant or controlled for [F(4, 144) = 126.725, p < .05, Partial ɳ2 = .779]. To ascertain the pairwise mean differences that were significant statistically, Pairwise Multiple Comparisons done revealed significant Mean Difference between each pairwise means in favour of the group that had longer daily Lumosity training. Thus, Lumosity training schedule can be used to overwhelmingly improve recall or memory.